Використання методів асептичної культури для розмноження рідкісних та високодекоративних представників тропікогенної флори - Lavrentyeva, A.N.; Ivannikov, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
Long-term researches of rare and ornamental tropical and subtropical plants micropropagation and the seed reproduction are summed up in this article. Seed and clonal propagation methods of many tropical and subtropical plants in culture in vitro are worked out. Optimum biotechnologies which permit to receive mass planting material are determined.